NGHIÊN CỨU ẢNH HƯỞNG CỦA pH VÀ DUNG MÔI ETANOL ĐẾN SỰ HÌNH THÀNH CANXI HYDROXY APATIT TỪ CANXI NITRAT - Hương, Đào Quốc; Linh, Dương Thuỳ (Vietnam Journal of Science and Technology, 2012)
SUMMARY STUDY  OF INFLUENCES OF pH AND ETHANOL ON FORMATION OF CALCIUM HYDROXYAPATITE The influences of different pH values and ethanol in the precipitation reaction of HA from Ca(NO3)2, (NH4)2HPO4 and NH3 were studied. The obtained samples were characterized by using methods such as XRD, FTIR, DTA/TGA and SEM. The results indicate, the pH values and ethanol play the important roles in the precipitation of single phase HA and their effectivity. Low pH values (< 7) lead to form the CaHPO4 phase, beside HA phase. The single phase HA formation can reach for the highest effectivity by 11 - 12 pH values. The high ethanol contents can also lead to CaHPO4 formation and increase the crystalline dimensions of HA particles. Keywords. Ca10(PO4)6(OH)2, Ca(NO3)2, (NH4)2HPO4, CaHPO4.